(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
Students give alms every day or what is known as SIBERSERI is a program launched by the Padang Pariaman Education and Culture Office as an effort to support the implementation of the independent curriculum and as a realization of the Padang Pariaman government’s vision and mission. This research aims to determine the process of implementing SIBERSERI as an effort to build the social care character of students at SMPN 1 IV Koto Amal. This research uses a qualitative method with a case study approach. The research informants were the head of the Padang Pariaman Education and Culture Office, the school principal, student affairs representatives, PAI teacher coordinator and 10 class VIII students. Data collection techniques through observation, interviews and documentation. Data were analyzed through data reduction, data presentation and drawing conclusions. Data validity techniques use source triangulation and technical triangulation. The research results show that the process of implementing SIBERSERI is carried out every day before the teaching and learning process begins. The results of the interviews show that the formation of social caring character in students can be well formed by getting students into the habit of giving alms every day.